Financial Performance Analysis of the Regional Government of Sigi Regency for the 2018-2023 Period - Nur Annisa Aulia; Rita Yunus; Eko Jokolelono; Andi Herman Jaya (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The main objective of this research is to assess the Financial Performance of the Regional Government of Sigi Regency from 2018 to 2023 by utilising a financial ratio analysis model including independence ratio, degree of decentralisation, efficiency and effectiveness of Local Own-Source Revenue (PAD), and regional expenditure compatibility ratio. The study relies on secondary data extracted from the Sigi Regency Budget Realisation Report (LRA). A quantitative descriptive approach was adopted for this analysis. The findings indicate that regional financial independence is alarmingly low, with a noticeable trend of reliance on central government funds. The degree of decentralisation is also critically lacking, exemplified by the minimal contribution of PAD to the overall regional revenue. On the other hand, the performance of local revenue sources is relatively positive, with revenue often surpassing the predetermined targets. However, the efficiency of financial management is still an obstacle, especially in the last few years where expenditures exceeded local revenues, thus reflecting the less than optimal use of the budget. The structure of regional expenditure also shows imbalances, with the dominance of operational expenditure being much greater than capital expenditure. These findings emphasize the importance of efforts to strengthen fiscal independence and improve efficiency in budget management to support the sustainability of development in Sigi Regency.